Comparison of adnexal torsion between pregnant and nonpregnant women - Hasson, Joseph; Tsafrir, Ziv; Azem, Foad; Bar-On, Shikma; Almog, Beni; Mashiach, Roy; Seidman, Daniel; Lessing, Joseph B.; Grisaru, Dan (American journal of obstetrics and gynecology, 2010)
The purpose of this study was to compare clinical manifestations, treatment, and pregnancy outcome of adnexal torsion in pregnant and nonpregnant women. We conducted a retrospective case-control study in the Departments of Gynecology at 2 tertiary centers between 1999-2008. Forty-one pregnant and 77 nonpregnant women with surgically proved adnexal torsion were assessed. Recurrence rate of torsion was 19.5% in pregnant women and 9.1% in control subjects; 73% of pregnant women conceived through assisted reproductive technologies. Doppler blood flow was falsely normal in 61% of pregnant women and in 45% of nonpregnant women; 83.3% of pregnant women delivered at term. Laparoscopic detorsion was the main surgical procedure. Presentation of adnexal torsion is similar in pregnant and nonpregnant women. Past assisted reproductive technology is an important risk factor in pregnancy. Doppler blood flow has a high false-negative rate and should not outweigh clinical suspicion. Although pregnancy outcome is favorable, the high rate of recurrence raises the issue of surgical fixation at the first episode.